Pengaruh Pendidikan Kesehatan Menggunakan Media Video Terhadap Perilaku Merokok Pada Remaja di SMA Negeri 5 Palu - Tosubu, Nivita Nanda Gabrela; Suaib, Suaib; Ahmil, Ahmil (Universitas Pahlawan Tuanku Tambusai, 2024)
Smoking behavior is an endanger to health, but there are still many smokers since adolescence age, especially males when they were teenagers. The use of good health education media can have an impact on smoking behavior in adolescents. In general, this research aims to determine the impact of health education media using video media on smoking behavior in adolescents at SMA Negeri 5 Palu. This type of research is an experiment with a quasi-experimental research design and a Nonequivalent control group design approach. The total sample was 34 respondents taken by used purposive sampling method. Analysis of research data using comparative tests with Independent t-tests. The results found that there is a significant difference in smoking behavior in the control group and the treatment group with the results (p?0.05), p-value = 0.001. The conclusion mentioned that there is a significant impact between health education using video media on smoking behavior in adolescents at SMA Negeri 5 Palu. It is expected that this research can be the reference of information for future researchers in influencing smoking behavior in adolescents by using other variables such as the influence of parents, peers, and cigarette advertisements.